Uni-vs. bilateral DIEP flap reconstruction – A multicenter outcome analysis. (September 2021) - Moellhoff, N.; Prantl, L.; Fritschen, Uv; Germann, G.; Giunta, R.E.; Kehrer, A.; Aung, T.; Zeman, F.; Broer, P.N.; Heidekrueger, P.I.
Abstract: Objective: Over the past decade numbers of bilateral mastectomy have increased steadily. As a result, bilateral breast reconstruction is gaining popularity. The presented study compares complications and outcomes of unilateral and bilateral DIEP free-flap breast reconstructions using the largest database available in Europe. Methods: Female breast cancer patients (n = 3926) receiving DIEP flap breast reconstructions (n = 4577 free flaps) at 22 different centers were included in this study. Free flaps were stratified into two groups: a unilateral- (UL) and a bilateral- (BL) breast reconstruction group. Groups were compared with regard to surgical complications and free flap outcome. Results: Mean operative time was significantly longer in the BL group (UL: 285.2 ± 107.7 vs. BL: 399.1 ± 136.8 min; p < 0.001). Mean ischemia time was comparable between groups (p = 0.741). There was no significant difference with regard to total (UL 1.8% vs. BL 2.6%, p = 0.081) or partial flap loss (UL 1.2% vs. BL 0.9%, p = 0.45) between both groups. Rates of venous or arterial thrombosis were comparable between both groups (venous: UL 2.9% vs. BL 2.2%, p = 0.189; arterial: UL 1.8% vs. BL 1.2%, p = 0.182). However, significantly higher rates of hematoma at the donor and recipient site were observed in the UL group (donor site: UL 1.1% vs. BL 0.1%, p = 0.001; recipient site UL 3.9% vs. BL 1.7%, p < 0.001). Conclusions: The data underline the feasibility of bilateral DIEP flap reconstruction, when performed in a setting of specialized centers. Highlights: Bilateral DIEP flap breast reconstruction is feasible when performed in specialized centers Bilateral DIEP flap breast reconstruction is not associated with a statistically significantly increased risk of flap loss. Bilateral and unilateral DIEP flap breast reconstruction show comparable rates of microvascular complications.